THE DILEMMA "FOR" AND "AGAINST" EUTHANASIA AND LEGAL AWARENESS OF THE DISABLED - Paraskeva Mancheva; Albena Kerekovska; Gergana Nenova (Peytchinski Publishing, 2016)
Aim: to study the legal awareness of the disabled and to solve the "for" or "against" euthanasia issue Material and methods: The study includes 305 polymorbid disabled people and is certificated by the General territorial Expert Medical Commission (LEDC) at University Hospital "St. Marina " Varna for the period October-December 2011. The study uses sociological method - direct and group inquiry and statistical methods: analysis (χ2), analysis of variance, correlation analysis (r), regression analysis (β). The processing of the results was performed by SPSS v.17.0 for Windows. Results: The study of the legal awareness of euthanasia revealed a need for more information among polymorbid disabled people. There is a discrepancy between their more positive, supportive attitude (acceptance of euthanasia) and lack of willingness to actually conduct. The reasons for this can be found in the sporadic public discussions on the debate on euthanasia and in the increased distrust of the health care system. Respondents believe that euthanasia at this stage cannot be imputed as an obligation for the Bulgarian medics. Conclusion: The legal public awareness issue is essential to protect the rights of the citizens, for the realization of those activities that require strict compliance with the Constitution, laws and regulations. The legal awareness study of the disabled for solution of the "for" or "against" euthanasia issue presents an opportunity to discuss a way out of a hopeless situation for patients in terminal condition.